The contribution of household chemicals to environmental discharges via effluents: Combining chemical and behavioural data. (1st March 2015) - Richards, Samia; Paterson, Eric; Withers, Paul J.A.; Stutter, Marc
Abstract: Increased concentrations and loads of soluble, bioavailable forms of phosphorus (P) are a major cause of eutrophication in streams, rivers and lakes in many countries around the world. To implement P control measures, it is essential to identify P sources and their relative load contributions. A proportion of P loading generated from household wastewaters is derived from detergents yet the P compositions of the range of domestic detergents and their usage is poorly understood. To quantify P loads from household detergents, we analysed a large range of detergents and cleaning products commonly available in the UK and Europe, comparing regular and eco-labelled products. Chemical data were coupled with survey results on typical household detergents preferences and usage (n = 95 households). We also determined whether the major and trace element signatures of these household detergents could potentially be used as anthropogenic tracers in watercourses. The greatest P concentrations were found for regular dishwasher detergents (43–131 mg P/g detergent) whilst the range of P in eco-labelled dishwasher detergents was much lower (0.7–9.1 mg P/g detergent). Other household cleaning groups contained relatively smaller P concentrations. Considering the survey results, detergents' total P loading generated from one household using either regular or eco labelled products, was 0.414 and 0.021 kg P/year, respectively. Given a household occupancy of 2.7, the P load from all detergent use combined was 0.154 kg P/person/year of which the dishwasher contribution was 0.147 kg P/person/year. In terms of elemental signatures, (DWD) dishwasher detergents were significantly ( P -value <0.001) different from other household cleaning products in their As, Na, TP, Si, Sr, SRP, Ti, Zn and Zr signatures. Na, P and B were all positively correlated with each other, indicating their potential use as a tracer suite for septic tank effluent in combination with other indices. We conclude that forthcoming legislation for reducing P contents in domestic laundry detergents will not address the dominant environmental P load from DWD and studies such as this are important in promoting and allowing scenarios of benefits from future legislation for DWD. Highlights: Detergent P contributes to eutrophication impacts from household sewage effluent. Approximately, 25% of P in wastewater is generated from detergents. Analysis of household chemicals was combined with a usage survey to quantify P load. Dishwasher detergents are the major contributors to P load from household chemicals. P impact can be limited by extending legislation to dishwasher detergents.